2012
DOI: 10.1002/jcb.24012
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral injection of taxol in vivo suppresses A549 tumor showing cytoplasmic vacuolization

Abstract: Based on our recent in vitro studies, this report was designed to explore the mechanism by which high concentration of taxol (70 µM) induced paraptosis-like cell death in human lung carcinoma (A549) cells, and to evaluate the therapeutic efficacy of taxol using A549 tumor-bearing mice in vivo. Exposure of cells to taxol induced time-dependent cytotoxicity and cytoplasmic vacuolization without the involvement of Bax, Bak, Mcl-1, Bcl-XL, and caspase-3. Although taxol treatment induced activating transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…We referred to this cell death form as parapotis-like cell death according to the similarity in morphology. [12][13][14] We have demonstrated that the taxolinduced vacuolization is from ER and mitochondrial; we have further demonstrated that caspases and Bcl-XL do not participate in the taxol-induced cytoplasm vacuolization. However, we have not delineated the taxol-induced cell death as paraptosis-like cell death or oncosis previously.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We referred to this cell death form as parapotis-like cell death according to the similarity in morphology. [12][13][14] We have demonstrated that the taxolinduced vacuolization is from ER and mitochondrial; we have further demonstrated that caspases and Bcl-XL do not participate in the taxol-induced cytoplasm vacuolization. However, we have not delineated the taxol-induced cell death as paraptosis-like cell death or oncosis previously.…”
Section: Discussionmentioning
confidence: 71%
“…EGFP was excited at 488 nm and°uorescence emission was recorded through a 500-550 nm band-pass¯lter. [12][13][14] In this study, 70 M of taxol was adopted in all experiments as described previously. 12,13 We used FCM analysis to assess the temporal relationship between the taxol-induced cytoplasm vacuolization and dissipation of ÁÉm.…”
Section: Monitoring Microtubule Distribution Inside Living Cells By Cmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that this altered ECM is a particular issue for nanoparticles due to the sheer size of the systems, particularly in comparison to free drug (Holback & Yeo, 2011). There has been a considerable amount of work done looking at intratumoral delivery of free anticancer drugs such as docetaxel (Yoo et al, 2010), cisplatin (Celikoglu et al, 2006a,b), and paclitaxel (Wang & Chen, 2012). Celikoglu group has produced some comprehensive reviews of the delivery of cytotoxic drugs by intratumoral injection, particularly via bronchoscopy and there appears to be a considerable opportunity to achieve even more in this treatment modality (Celikoglu et al, 2008(Celikoglu et al, , 2010.…”
Section: Intratumoral Injectionmentioning
confidence: 99%
“…In an effort to further reduce tumour mass and improve outcomes of therapeutic bronchoscopy in patients with malignant airway obstruction, the intratumoral administration of chemotherapeutic agents has been proposed as an adjunctive therapy. In animal models and in patients with lung cancer, this approach has demonstrated successful results in delaying tumour recurrence . A new drug delivery catheter, the Blowfish Transbronchial Micro‐Infusion Catheter (Mercator MedSystems, Emeryville, CA, USA) was developed to directly deliver medication safely and reliably into the airway wall by way of a microneedle port.…”
Section: Introductionmentioning
confidence: 99%